2019
DOI: 10.1108/jabs-04-2018-0135
|View full text |Cite
|
Sign up to set email alerts
|

Views of Indonesian consumer towards medical tourism experience in Malaysia

Abstract: Purpose Indonesians are known for their unique behaviour and willingness to travel abroad for healthcare treatments. More than half of the healthcare “tourists” who travel to Malaysia come from Indonesia, followed in numbers by those in India, Japan, and China, Libya, the UK, Australia, USA, Bangladesh and the Philippines. Malaysia is also geographically located near two Indonesian main islands, i.e. North Sumatera and North Kalimantan. These reasons contribute to making Indonesia one of the most productive he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…theory of planned behavior, SERVQUAL model, etc.) (Chaulagain et al, 2020;Saragih and Jonathan, 2019;Liang et al, 2019), no comprehensive scale has been found to measure the overall experience of medical tourists. In this backdrop, Ghosh and Mandal (2019) developed and validated a comprehensive MTEX measurement scale based on a grounded theory approach.…”
Section: Medical Tourism Experience and The Mtex Modelmentioning
confidence: 99%
“…theory of planned behavior, SERVQUAL model, etc.) (Chaulagain et al, 2020;Saragih and Jonathan, 2019;Liang et al, 2019), no comprehensive scale has been found to measure the overall experience of medical tourists. In this backdrop, Ghosh and Mandal (2019) developed and validated a comprehensive MTEX measurement scale based on a grounded theory approach.…”
Section: Medical Tourism Experience and The Mtex Modelmentioning
confidence: 99%
“…As a result, the economic significance of medical tourism in the Malaysian marketplace is growing. Almost 60% to 70% of the inbound patients that visited Malaysia are from Indonesia, followed by other countries in the Middle East, India, China, Japan, Australia, New Zealand and the United Kingdom ( 21 – 22 ). The Malaysian Healthcare Travel Council (MHTC) Commercial Division Chief Officer, Nik Yazmin Nik Azman, stated that over 670,000 Indonesian nationals went to Malaysia for medical treatments and hospitality in 2018 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such trends prompt neighbouring countries such as Singapore and Thailand to promote medical tourism—primarily due to the perceived economic benefits of this sector ( 28 ). Notably, Indonesians prefer to travel to Malaysia for cardiac treatment ( 22 ). However, the rationale for choosing Malaysia as their medical destination was not holistically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The number of specialist doctors from Indonesia who have become medical experts in hospitals abroad, and the various natural beauties in Indonesia will be able to position Indonesia as one of the countries in Asia having the opportunity to garner a large market. But so far Malaysia has been more successful than Indonesia [17]. Thus, it is important to conduct this research to compare the model of developing medical tourism-based medical services, hence the hospitals and related institutions in Indonesia can develop more successfully and become targets for domestic and foreign residents in checking their health; and for the government which is a must to make efforts to reduce the tendency of Indonesian citizens to seek treatment abroad.…”
Section: Introductionmentioning
confidence: 99%